The Correlation Between Parenting Style And Development Preschool Children - Tia Winda Windar Tika; Dede Gantini; Sinar Pertiwi (Poltekkes Kemenkes Semarang, 2021)
Background: Family influence in the formation and development of the child's personality is very great because the family is the first social group where children can interact, where children learn and declared themselves as social beings. Families can also provide a basis for the formation of behavior, character, morals, and education for children. Parenting is the attitude of the parents interacts with their children. The purpose of this research was to determine the relationship of parenting parents with the development of preschool children in kindergarten Aisyiah Tawang District of Tasikmalaya.Methods: the methods used is a quantitative research using a cross-sectional design. The population in this study all students kindergarten in kindergarten Aisyiah Tasikmalaya, preschool, and their parents who totaled 43 people. The sampling technique in this research is using saturation sampling technique, with a total sample of 43 children and their parents.Results: The results showed that the greatest percentage of parents' parenting preschoolers in kindergarten Aisyiah Tasikmalaya city is with positive parenting, the largest percentage growth of preschool children is to have appropriate development. Statistical test results stated that there is a significant relationship between parenting parents with preschool-age child development.Conclusion: Most parenting preschoolers in kindergarten Aisyiah Tasikmalaya categorized as positive and progress is being made by his age.